2023
DOI: 10.1021/acs.iecr.2c03743
|View full text |Cite
|
Sign up to set email alerts
|

Green Phosphate Route of Regeneration of LiFePO4 Composite Materials from Spent Lithium-Ion Batteries

Abstract: To develop efficient, viable, and promising routes to regenerate nano-LiFePO4 (nano-LFP) composite materials from spent LFP batteries, this paper studied phosphate approaches by taking Li3PO4 and FePO4 as raw materials. The crystalline structure, morphology, and physicochemical properties of regenerated LiFePO4 nanoparticles were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and electrochemical measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…These two kinds of carbon as electronic conductive skeleton, and LiF and Li 2 O as ionic conductive base, them forming a dual conductive network to facilitate lithium storage [31] . At the same time, it can be seen that there are flocculated carbon network connections between the particles, which is conducive to the transfer of electrons [1c] . Carbon coating on the surface helps to improve the electrochemical properties and prevent excessive grain growth [32] …”
Section: Resultsmentioning
confidence: 99%
“…These two kinds of carbon as electronic conductive skeleton, and LiF and Li 2 O as ionic conductive base, them forming a dual conductive network to facilitate lithium storage [31] . At the same time, it can be seen that there are flocculated carbon network connections between the particles, which is conducive to the transfer of electrons [1c] . Carbon coating on the surface helps to improve the electrochemical properties and prevent excessive grain growth [32] …”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously, the nitrogen atoms derived from the amino group integrate into the carbon layer, creating additional active sites and enhancing the electrical conductivity of the LFP particles. The resultant regenerated LFP manifests commendable electrochemical performance, exhibiting an impressive capacity retention of 86 % even after 500 cycles at a high rate of 5 C. A large number of studies have conclusively demonstrated the feasibility of regenerating spent LFP directly from LiFePO 4 through various methods, including solid-phase sintering, molten-salt reduction, [71] hydrothermal reduction, [72] and electrochemical treatment. Despite these findings, the pragmatic application and economic viability of these techniques necessitate further scrutiny.…”
Section: Direct Regeneration Based On the Reductionmentioning
confidence: 99%
“…The pyrometallurgy process of using high-temperature calcination benefits from the simplicity of the process and can be used on a large scale, but this method consumes a lot of energy and produces a large amount of greenhouse gases (GHGs). [15][16][17][18] The hydrometallurgy process uses chemicals such as mineral acids to selectively leach metal elements from the positive electrode material of LIBs and recover various elements through fractional precipitation. It is widely prevalent because of the high-purity products, but the hydrometallurgy process needs to consume a large amount of chemical reagents and water.…”
Section: Introductionmentioning
confidence: 99%